MIGRASI DATABASE DENGAN MENGGUNAKAN SSIS (SQL SERVER INTEGRATION SERVICE) DI PT XYZ INDONESIA - Satria Andoko, Banni (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2010)
PT. INDONESIA XYZ is the largest Direct Selling company in Indonesia that have strong growth in comparison with other Direct Selling companies in Indonesia. With the rapid development of PT XYZ INDONESIA, then decided to update its sales application that can not follow the process of starting a thriving business. In addition the needs of data storage capacity becomes very large. To be able to meet that need, so the new system required a more reliable and faster in performance. By looking at the problem, we needed a system / application that can move and manipulate the old data so it can be used by the new system. Database migration process is designed using one of the facilities provided by MS SQL 2005, the facility is named SSIS (SQL Server Integration Service).Â Keyword : Data Migration, SSIS, ETL, MsSQL 2005, RDBS, SQL Query